Introducing a Cat Tool to Translate: Wordfast - Apriliana, Fika; Kurniawan, Ardiyarso; Ferianda, Sandy; Kastuhandani, Fidelis Chosa (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2016)
This article aims at introducing CAT tools to those prospective translators who are familiarwith with the tools for the first time. Some of the CAT tools must be paid for while someothers are free. This article is to inform the readers about the list of free and paid CAT tools,advantages and disadvantages of those tools. One does not need special training for using afree CAT tool while using the paid CAT tools, one needs some special preparation. Thisarticle is going to focus more on Wordfast Pro as the second most widely used CAT toolsafter SDLTrados. Wordfast Pro is a paid software the functioning of which is based on thecreation of a Translation Memory which facilitates and speeds up the translator's work. Thisarticle is going to briefly explain the advantages of Wordfast Pro and the steps of using it.The translation example is presented to reveal the different translation results of Wordfast Proas a paid CAT tool and OmegaT as a free CAT tool. Therefore, the article will facilitate thosewho intend to know more about Wordfast Pro and start using it. Keywords: CAT tools, Wordfast Pro, OmegaT